Reinstatement of Sapium sceleratum (Euphorbiaceae), an endemic species from Northeast Brazil, and new circumscription of Sapium argutum - Cordeiro, Wesley Patrício Freire De Sá; Melo, André Laurênio De; Athiê-Souza, Sarah Maria; Esser, Hans-Joachim; Sales, Margareth Ferreira De (Phytotaxa, 2018)
This paper includes the reinstatement of Sapium sceleratum with one new synonym (Sapium cicatricosum). In addition, a new circumscription is presented for Sapium argutum and the second-step lectotypification of the name Excoecaria arguta, as well as an identification key for the species of Sapium from North-east Brazil, illustrations and comments on geographic distribution and habitat of S. argutum and S. sceleratum.